2022
DOI: 10.1093/gbe/evac042
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Level Reference Genomes for Two Strains of Caenorhabditis briggsae: An Improved Platform for Comparative Genomics

Abstract: The publication of the Caenorhabditis briggsae reference genome in 2003 enabled the first comparative genomics studies between C. elegans and C. briggsae, shedding light on the evolution of genome content and structure in the Caenorhabditis genus. However, despite being widely used, the currently available C. briggsae reference genome is substantially less complete and structurally accurate than the C. elegans reference genome. Here, we used high-coverage Oxford Nanopore long-read and chromosome conformation c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 91 publications
(168 reference statements)
0
29
0
Order By: Relevance
“…To test whether the msft-1/tlpr-1 TA is indeed mobile in nature, we assembled the genomes of three additional C. briggsae wild isolates using Nanopore long-05 reads (Figure S6). Analysis of these three and two additional genomes [31] revealed that the insertion site of msft-1/tlpr-1 varied between natural isolates. msft-1/tlpr-1 was located on Chr.…”
Section: Msft-1/tlpr-1 Is a Novel Mobile Selfish Ta Elementmentioning
confidence: 99%
“…To test whether the msft-1/tlpr-1 TA is indeed mobile in nature, we assembled the genomes of three additional C. briggsae wild isolates using Nanopore long-05 reads (Figure S6). Analysis of these three and two additional genomes [31] revealed that the insertion site of msft-1/tlpr-1 varied between natural isolates. msft-1/tlpr-1 was located on Chr.…”
Section: Msft-1/tlpr-1 Is a Novel Mobile Selfish Ta Elementmentioning
confidence: 99%
“…elegans and C . briggsae , where crossing-over rarely occurs [ 19 , 20 , 54 ]. Thus, absence of a perfect genotype-phenotype correlation could be interpreted in at least two not mutually exclusive ways.…”
Section: Discussionmentioning
confidence: 99%
“…This interval also contains the PCR genotyping assay at 4.0 Mbp that was previously used to map delay, at which 1 of 41 delayed individuals did not contain a homozygous AF16 genotype [12]. Genetic mapping is notoriously difficult in the central recombination domains in C. elegans and C. briggsae, where crossing-over rarely occurs [19,20,54]. Thus, absence of a perfect genotype-phenotype correlation could be interpreted in at least two not mutually exclusive ways.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations